Directorial treatment of character psychological transformations in cinema and television (Al-Academy, 2024)
This research deals with the most important element of the dramatic construction, which is the cinematic character within the cinematic image space, and the ways in which the character is transformed and adapted to film events, through verbs and reactions with the rest of the movie characters, as the researcher divided the research into five chapters, so the first chapter was The title carries (the systematic framework), which contained (the research problem that ended with the following question: the modalities and mechanisms of direct treatment of the psychological transformations of the character in the movie film ?, And then the importance of the research, the research goals, and the limits of the research, and then the researcher concluded by defining the terms), either The second chapter, which carries the title (theoretical framework and previous studies), which the researcher divided into two topics, the first outlines the title (psychological transformations of personality), the researcher addressed the theorists' views on personal transformation psychologically, and the researcher reinforced these views with film examples, while the second topic that carries the title (personality in The movie) In this topic, the researcher discussed the role of the cinematographer and how to treat and employ it within the cinematic space. As for the third chapter that carries the title (research procedures), which is divided into (research methodology, research community, research sample, research tool, validation of the tool, and this chapter is concluded with the unit of analysis, while the fourth chapter that carries the title (sample analysis) at the time the researcher analyzed the film Foreigner (JOKER) Joker produced 2019. As for the fifth chapter, which included (the results, conclusions, proposals, recommendations, sources, appendices. The most important results were:1. The actor's ability to master and personalize the character has an important role in highlighting the psychological aspect of the character.2. Photography and lighting have an important role in highlighting the psychological dimension of the personality.3. The actions and reactions of the personality that highlight the psychological transformation of the personality.4. The story events are associated with the verbs to be the psychological aspect of the character.5. The characters surrounding the main character have a role in showing the psychological dimension of the character.6. Gestures have a role in highlighting the personality's psychological side.Then the chapter was concluded with an English language summary.